2009
DOI: 10.1002/elps.200800333
|View full text |Cite
|
Sign up to set email alerts
|

Modified cyclodextrins for fast and sensitive chiral‐capillary electrophoresis‐mass spectrometry

Abstract: In this work, three modified CDs (mCDs), namely 6-deoxy-6-[1-(2-amino)ethylamino]-beta-CD, 6-deoxy-6-[N-(2-methylamino)pyridine)]-beta-CD and 3-monodeoxy-3-monoamino-beta-CD, are investigated as chiral selectors for CE with LIF (CE-LIF) and CE-TOF-MS. The potential of these three mCDs as chiral selectors in CE was also compared with the unmodified beta-CD and gamma-CD. A group of ten different D- and L-amino acids derivatized with FITC was selected as case-study for CE-LIF and CE-MS comparison. The analyte gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 68 publications
0
54
0
3
Order By: Relevance
“…Interestingly, 4-hydroxy-l-threonine seemed to disappear in the transgenic soybean compared to its parental non-transgenic line. In a separate report, herbicide-resistant transgenic soybean was characterized by Giuffrida et al using a novel chiral CE-ESI-TOF-MS method [94]. In that research, the obtained D/L-amino acid profiles were very similar for conventional and GM soybean.…”
Section: Ms-based Technologiesmentioning
confidence: 91%
“…Interestingly, 4-hydroxy-l-threonine seemed to disappear in the transgenic soybean compared to its parental non-transgenic line. In a separate report, herbicide-resistant transgenic soybean was characterized by Giuffrida et al using a novel chiral CE-ESI-TOF-MS method [94]. In that research, the obtained D/L-amino acid profiles were very similar for conventional and GM soybean.…”
Section: Ms-based Technologiesmentioning
confidence: 91%
“…Detection by electrospray-mass spectrometry (ESI/MS) is now a well-established technique in CE [25][26][27] and, recently [28], some of us carried out a study, simultaneously separating different enantiomeric pairs of fluorescent amino acids derivatives in CE with laser-induced fluorescence (LIF) detection and CE-TOF-MS, by using SID CD as a selector. The investigation showed that MS can be conveniently used as alternative detection technique, and that the usual thinking that the presence of CDs in the background electrolyte (BGE) prevents the use of MS detection has exceptions.…”
Section: Introductionmentioning
confidence: 99%
“…em relação a cromatografia liquida é seu limite de detecção relativamente pobre em relação à cromatografia liquida (Giuffrida et al, 2009). …”
Section: Viviane Do Nascimento Análise Confirmatória De Alcalóides Pounclassified
“…Deste modo, a CE-MS quiral permite combinar a velocidade de separação, poder de resolução elevado, mínimo de amostra e reagentes são consumidos na CE e com as informações fornecidas pelo MS (Giuffrida et al, 2009). fornecida por este tipo de montagem é fortemente dependente da composição qualitativa e quantitativa do eletrólito utilizado para separação, assim como do líquido auxiliar.…”
Section: Viviane Do Nascimento Análise Confirmatória De Alcalóides Pounclassified
See 1 more Smart Citation